Lessons from the “life-world”: the late Husserl and the critique of objectivism (Scientiae Studia, 2004)
The phenomenological opposition to the idealized nature of modern science has already feed the antiscientificism of many. Objecting to such appropriation, in this article one aim at to recover the meaning of Husserl's observations about Galileo, inserting them in the phenomenological proposal of enlargement of the rationality.